THE ANALYSIS OF INDONESIAN CONSUMER PREFERENCES TOWARDS INDONESIAN LOCAL LIPSTICKS - Kardena, Syifa Aida; Hudrasyah, Herry (Journal of Business and Management, 2017)
Abs tract.The cosmetic industry is one of the fastest growing sec tors in Indonesia and has consistently recorded double - digit growth in recent years. The growth of cosmetic industry in Indonesia is always increasing every year. In the period of 2010 – 2015 the total average Indonesia cosmetic industry growth is around 9 .67% every year. The preliminary study result shows lipstick is the most wanted cosmetic product in this research. In recent years, Indonesian local lipstick is on the rise, there are many local lipstick brands in the mark et. Nevertheless, more and more new local lipstick brands companies entering the mark et in Indonesia, resulted into a highly competitive environment. Therefore, it is essential for the companies to continuously develop their business activities and product development in order to remain an d attract new customers. The purpose of this study is to find out the important factors for Indonesian customer towards Indonesian local lipstick and analyze the important attributes for the customer. This study is using both qualitative and quantitative m ethod, focus groups discussion and conjoint analysis. The results shows the preferred combination are Rollover reaction, natural color, soft matte texture, beauty blogger/vlogger review and price value at 50.000 rupiah. The most important attribute based on the result is brand